Epidemiological investigations on Trypanosoma evansi infection in dromedary camels in the South of Algeria - Djamila Boushaki; Amel Adel; Mamadou Lamine Dia; Philippe Büscher; Hafsa Madani; Brahim Aymard Brihoum; Hassiba Sadaoui; Nadera Bouayed; Nadia Kechemir Issad (Heliyon, 2019)
An epidemiological study of Trypanosoma evansi (T. evansi) infection in dromedaries was conducted in four wilayate (localities) of Southern Algeria: Béchar, El Bayadh, Ouargla, Tamanrasset. Between February 2014 and April 2016, 1056 camels of different ages and both sexes from 84 herds were sampled. The prevalence was determined through parasitological examination (Giemsa stained thin smear, GST), serological tests (CATT/T. evansi, ELISA/VSG RoTat 1.2, immune trypanolysis), and molecular tests (T. evansi type A specific RoTat 1.2 PCR and T. evansi type B specific EVAB PCR).The overall prevalence was 2.4 % with GST, 32.4% with CATT/T. evansi, 23.1% with ELISA/VSG RoTat 1.2, 21.0% with immune trypanolysis (TL), 11.2 % with RoTat 1.2 PCR and 0% with EVAB PCR.El Bayadh was the most affected wilaya with 11.8% positives in GST, 74.9% in CATT/T. evansi, 70.1% in ELISA/VSG RoTat 1.2 and 62.2% in immune trypanolysis. Only in Béchar, a non-significantly higher prevalence (13.6%) was observed with RoTat1.2 PCR than in El Bayadh (13.0%). We didn't find any evidence of the presence of T. evansi type B in the study area.